آراء المدرسين نحو الترجمة من العربية إلى المادورية في كتاب تربية الصبيان للفاضل محمد حبيب الله بن رئيس إبراهيم في بلنجائن(دراسة تحليلة استقبالية) - Umar Bukhory; Rousul Firdaus (IAIN MADURA, 2017)
This research article focuses on the reception analysis about the opinions and comments of the teachers of Madrasah Ibtidaiyah and Madrasah Diniyah in Palengaan District, Pamekasan toward the translation of Tarbiyatus Shibyan book by Habibullah Bin Rais Ibrahim, the leader of Al-Is’af Islamic Boarding School, Klaba’an, Sumenep. This research reports about the general opinion of the teachers about the translation of that book as well as their opinions about the weaknesses and advantages of Arabic to Madurese translation in this book, for instance about the use of less suitable words (harsh words) and the use of some words are difficult to understand because of too polite (ancient). For example, the in giving the meaning of the word غائط, it is translated by the word “taeh (a very impolite Madurese language of ‘feces’)”, it should be changed by using more polite word of “tenjeh” to be better to hear. And also, the use of ancient Madurese language such as أبنداغ، ننداغه، لوداغ, etc which should also be changed by using more understandable words.